Neopagan groups and the Seasonal Celebration of the Natural Cycles: Epistemological and Ontological challenges on the study of spirituality - Martins, Joana. (VII Congresso Associação Portuguesa de Antropologia, 2019)
Neopaganism, an “umbrella term” used to designate several religious and spiritual polytheistic traditions, has as its main beliefs nature as sacred, polytheism and gender equality. Through the seasonal celebration of the natural cycles, they look for the establishment of a connection with the natural world based on respect and protection. With the ritualization of the seasonal festive and natural cycles it’s possible to understand that this is the field where relationships, sociability and world views are created and transported to the establishment of important relationships between humans and non-humans, as well as to ethical and moral concerns of ecological order, that also are epistemological and ontological. Working with this dimension of the lived religion and spirituality allows us to question and reflect not just about the way we conduct our anthropological work, and question the way it was done until now, but also the challenges and answers that arise, and the importance that this new religious movements face due to the pollical, sociocultural and ecological crisis that mark the contemporary life. If one considers the alternative discourses and solutions that they present, an important and genuine dialogue can be created between Anthropology and these groups.